A Novel Platform of MOF for Sonodynamic Therapy Advanced Therapies - Donghui Liao; Jiefeng Huang; Chenyi Jiang; Luyi Zhou; Mingbin Zheng; Alireza Nezamzadeh-Ejhieh; Na Qi; Chengyu Lu; Jianqiang Liu (Pharmaceutics, 2023)
Metal–organic frameworks (MOFs) combined with sonodynamic therapy (SDT) have been introduced as a new and efficient treatment method. The critical advantage of SDT is its ability to penetrate deep tissues and concentrate energy on the tumor site to achieve a non-invasive or minimally invasive effect. Using a sonosensitizer to generate reactive oxygen species (ROS) under ultrasound is the primary SDT-related method of killing tumor cells. In the presence of a sonosensitizer, SDT exhibits a more lethal effect on tumors. The fast development of micro/nanotechnology has effectively improved the efficiency of SDT, and MOFs have been broadly evaluated in SDT due to their easy synthesis, easy surface functionalization, high porosity, and high biocompatibility. This article reviews the main mechanism of action of sonodynamic therapy in cancer treatment, and also reviews the applications of MOFs in recent years. The application of MOFs in sonodynamic therapy can effectively improve the targeting ability of SDT and the conversion ability of reactive oxygen species, thus improving their killing ability on cancer cells. This provides new ideas for the application of micro/nano particles in SDT and cancer therapy.